2012
DOI: 10.1242/jcs.096792
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise androgen receptor dimerization

Abstract: SummaryAndrogen-regulated gene expression is a highly coordinated dynamic process mediated by androgen receptor (AR) ligand binding and DNA binding, and by specific AR protein-protein interactions. The latter include DNA-binding domain (D-box) interactions in AR homodimers, and the interaction of the FQNLF motif in the AR N-terminal domain and the coactivator groove in the ligand-binding domain (N/C interaction). We have studied these interactions in AR homodimerization using quantitative imaging techniques. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
139
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(148 citation statements)
references
References 45 publications
(82 reference statements)
7
139
0
2
Order By: Relevance
“…This mutant, in which the mutated amino acid is important for base-specific interaction with AR target sequences in DNA (Shaffer et al, 2004), has been found in a patient with complete androgen insensitivity syndrome (Sultan et al, 1993). In line with these findings, it was shown that this AR mutant is transcriptionally inactive (Lobaccaro et al, 1999) and lacks stable binding to DNA (van Royen et al, 2012). Taken together, these data suggest that the R585K mutation disrupts specific interaction of ARs with their target sites in the genome.…”
Section: Quantitative Analysis Of Individual Ar Dynamicssupporting
confidence: 58%
See 1 more Smart Citation
“…This mutant, in which the mutated amino acid is important for base-specific interaction with AR target sequences in DNA (Shaffer et al, 2004), has been found in a patient with complete androgen insensitivity syndrome (Sultan et al, 1993). In line with these findings, it was shown that this AR mutant is transcriptionally inactive (Lobaccaro et al, 1999) and lacks stable binding to DNA (van Royen et al, 2012). Taken together, these data suggest that the R585K mutation disrupts specific interaction of ARs with their target sites in the genome.…”
Section: Quantitative Analysis Of Individual Ar Dynamicssupporting
confidence: 58%
“…This variation is mostly caused by differences in the choice of analytical methods and by different assessment of experimental parameters regarding microscopic properties, such as the laser intensity distribution or photophysical properties Agonist (R1881)-bound AR shows a typical speckled distribution whereas the mutant AR R585K, which has a point mutation in the DNA-binding domain disabling interactions with the cognate AR target sequence, is homogeneously distributed in the presence of R1881 (see also van Royen et al, 2012). When bound with antagonist (OHF), both wild-type (wt) and the R585K mutant AR show a more homogeneous distribution.…”
Section: Discussionmentioning
confidence: 99%
“…A similar strategy was used to clone the AR-DBD Ļ© hinge into the Pan4 vector (avidity) expressing the N-terminal biotinylation sequence (GLNDIFEAQKIEWHE) and C-terminal His tag. YFP-AR plasmid was a gift from Dr. Jan Trapman (28) and is based on pEYFP-C1 (Clontech). YFP-V7 was constructed by polymerase incomplete primer extension method using the following primers and templates: AR-V7 insert from pcDNA3.1 AR-V7 template 5Šˆ-GGT GCT GGA GCA GGT GCT GGA ATG GAA GTG CAG TTA GGG CTG and 5Šˆ-GGA AAT AGG GTT TCC AAT GCT TCA GGG TCT GGT CAT TTT GAG; pEYFPC1 vector lacking the full-length AR 5Šˆ-CAG CCC TAA CTG CAC TTC CAT TCC AGC ACC TGC TCC AG and 5Šˆ-CTC AAA ATG ACC AGA CCC TGA AGC ATT GGA AAC CCT ATT TCC.…”
Section: Methodsmentioning
confidence: 99%
“…To test this idea, we transfected PC3 cells with plasmids encoding YFP-tagged full-length AR (yellow fluorescent protein, YFP-AR, see Ref. 28) and splice variant AR-V7 (YFP-V7). Both YFP-AR and YFP-V7 were able to drive luciferase expression and could be inhibited by VPC-14228/14449, demonstrating that the YFP tag did not affect AR transcriptional activity or compound inhibition (Fig.…”
Section: Dbd-interacting Compounds Do Not Impede Ar Nuclear Translocamentioning
confidence: 99%
“…C-NMR spectra, in addition to the distortionless enhancement by polarization transfer (DEPT) spectrum, of 1 presented similar properties with lindelofidine. 8) The additional spectra signals corresponding to necic acid moiety properties include Ī“ H 6.91 (1H, dd, J=7.0, 6.5 Hz, H-13), 4 C-NMR and DEPT spectra, which displayed the remaining signals of the two carbonyl carbons at Ī“ C : 175.9 (C-16) and 162.0 (C-11), and a quaternary carbon at Ī“ C : 128.5 (C-12). In the correlation spectroscopy (COSY) spectra, the correlated signals between H-13/H-14 as well as H-17/H-18/H-19 and H-20 were observed.…”
Section: Resultsmentioning
confidence: 99%